Procrastination and its effect on English writing errors and writing performance of medical students - Kafipour, Reza; Jafari, Samaneh (Universitas Pendidikan Indonesia, 2021)
This study aims to investigate the relationship between procrastination and students’ writing performance. It also seeks to find a correlation between students’ writing error types and procrastination. The study followed a quantitative-survey design that utilized a writing test and a questionnaire to collect data using a convenience sampling method from 44 medical students at a university in Iran. Descriptive and inferential statistics were used to analyze data. Based on the results, the most frequently occurred errors were developmental errors followed by others and ambiguous errors. Interlingual errors were found as the least frequently occurred errors. Besides, procrastination was strongly and negatively correlated with and contributed to the students’ writing performance. Finally, procrastination contributed to all four types of errors made by the students as the dependent variable’s variance value correlated significantly with all the independent variables. As some implications of this study, teachers can learn about learners’ writing error types and inform their instruction. Additionally, this can help instructors develop methods that can help decrease procrastination levels among learners.